One-pot low-temperature preparation of thermo-responsive self-ceramifiable glass fiber insulation tiles with exceptional mechanical and ablative properties - Fengchun Ji; Zhihang Peng; Xin Yang; Jian Feng; Yang Xiang; Zeyu Liu (Journal of Materials Research and Technology)
Ceramic fiber rigid insulation tiles (CFRITs) provide a feasible solution for thermal protection of aerospace vehicles in extreme environments. However, traditional CFRITs’ high forming temperature and non-ablative property limit their applications. The study first introduces a novel thermo-responsive self-ceramifiable glass fiber rigid insulation tile (GFRIT) characterized by low forming temperature (150 °C), low density (0.435 g/cm3), high compressive strength (1.58 MPa), and low thermal conductivity (0.0553 W/(m·K)) in normal circumstances. Interestingly, it can spontaneously transform into high-strength semi-crystalline ceramics at elevated temperatures. The self-ceramization mechanism of GFRIT is elaborated in considerable detail. The 20 mm thick sample shows low backside temperature only 216 °C, solid overall structure, and near-zero ablation after continuous burning at 1300 °C for 600 s. The detailed illustration of gradient inter-coupling effects among various thermal protection mechanisms is provided. The self-ceramifiable GFRIT offers a significant idea for developing thermal protection materials (TPMs) with processability, toughness, high load-carrying capacity and efficient insulation in extreme conditions.